Indonesian Efforts and Delays in Forest Law Enforcement, Governance and Trade (FLEGT )License Implementation within the European Union - Oswiputra, Raihan Fadhil (JLAST : Journal of Law and Social Transformation, 2023)
The purpose of this article is to analyze the factors contributing to Indonesia's evolving stance during negotiations for issuing FLEGT Licenses, employing qualitative research techniques and a single case study approach. Stephen Woolcock's Economic Diplomacy Theory is utilized as the analytical framework. This paper argues that structural, domestic, and ideological factors influence Indonesia's policy adjustments in response to the FLEGT license mechanism. The study reveals issues such as an imbalanced relationship between Indonesia and the EU in FLEGT implementation, policy inconsistencies among Indonesian governmental bodies involved, and perceptual discrepancies among stakeholders engaged in the process. The findings suggest that, in Indonesia's case, Woolcock's theory factors interact, with the pivotal relationship between interest and institutional variables within the domestic decision-making process significantly impacting changes in Indonesia's stance on economic diplomacy practices